2023
DOI: 10.2174/1574888x17666220926115240
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Hydrogen Promotes Adipose-derived Stem Cell Myogenic Differentiation via Regulation of Mitochondria

Abstract: Background: Acute skeletal muscle injuries are common physical or sports traumas. Cellular therapy has excellent potential for regeneration after skeletal muscle injury. Adipose-derived stem cells (ADSCs) are a more accessible type of stem cell. However, it has a low survival rate and differentiation efficiency in the oxidative stress-rich microenvironment after transplantation. Although molecular hydrogen (H2) possesses anti-inflammatory and antioxidant biological properties, its utility in mitochondrial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…Accumulating evidence suggests that oxidative stress characterized by the excess generation of reactive oxygen species is a key factor in the low cell survival rate of transplanted MSCs [ 62 ]. Antioxidant drugs have been used to overcome oxidative stress and enhance MSC survival in vitro (Table 3 ).…”
Section: Msc Transplantation and Homing Process In Vivomentioning
confidence: 99%
“…Accumulating evidence suggests that oxidative stress characterized by the excess generation of reactive oxygen species is a key factor in the low cell survival rate of transplanted MSCs [ 62 ]. Antioxidant drugs have been used to overcome oxidative stress and enhance MSC survival in vitro (Table 3 ).…”
Section: Msc Transplantation and Homing Process In Vivomentioning
confidence: 99%
“…Another recent 2023 study demonstrated that molecular hydrogen plays a crucial role in promoting myogenic differentiation in adipose-derived stem cells (ADSCs) for potential therapeutic applications in skeletal muscle injuries [ 32 ]. The study investigated the protective effects of H 2 on ADSCs using various assays, including the MTT assay, live–dead cell staining, Western blot analysis, immunofluorescence staining, confocal imaging, and transmission electron microscopy.…”
Section: A Historical Journey: the Convergence Of Molecular Hydrogen ...mentioning
confidence: 99%
“…The results indicated that an appropriate volume fraction of H 2 significantly reduced mitochondrial reactive oxygen species levels, increased the number of mitochondria, and induced mitophagy. These effects collectively enhanced the survival and myogenic differentiation of ADSCs [ 32 ]. These findings suggest the promising application of H 2 in addressing skeletal muscle diseases and pathologies associated with mitochondrial dysfunction.…”
Section: A Historical Journey: the Convergence Of Molecular Hydrogen ...mentioning
confidence: 99%
“…Оба указанных противоречия можно объяснить, если предположить, что H 2 функционирует не только как поглотитель радикалов, но и как фактор, вызы вающий митохондриальный гормезис (адаптивную реакцию), и тем самым противодействующий ОС в клетках [30]. Показано, что H 2 стимулировал мито фагию [31] -процесс утилизации поврежденных мито хондрий со сниженным потенциалом. В таком случае повышение мембранного потенциала митохонд рий будет наблюдаться только через какоето время по сле воздействия водорода, когда популяция митохон дрий успеет обновиться.…”
Section: противоречия в эффектах H 2 и их объяснениеunclassified